Allergic contact dermatitis and vulvar dermatoses. - Marren, P; Wojnarowska, F; Powell, S (1992)
Vulval itch and discomfort are often intractable symptoms and the response to standard therapy can be unsatisfactory. There is some evidence that vulvar sensitivity to irritants is higher than that of forearm skin, but the incidence of relevant allergic contact sensitivity amongst this patient population is unknown. The patch-test data over a 5-year period of 135 patients with persistent vulval symptoms were reviewed and 63 patients had positive results. Of these, 39 had positive results considered to be relevant to their clinical condition. Medicaments and their constituents were responsible for most of these reactions and more than half the patients had multiple allergies.